Axel Springer AG v. Germany, or: how to perform limited review - Borowski, Martin (The Rule of Law in Europe, 2021)
The decision Axel Springer AG v. Germany of the Grand Chamber is an example of Drittwirkung or horizontal effect of rights under the Convention. Just as German domestic courts, the ECtHR had to ensure the balance of the freedom of expression and the right to protection of the private life. In these cases, the task of the Court is to make a “limited review” of the decisions of the domestic courts against the backdrop of domestic statutes. Limited review in the sense of the margin of appreciation is an expression of this subsidiarity. Whereas in the case of strict review, there are only two outcomes (correct result/wrong result), in limited review, there are three possible outcomes: (i) substantively fully correct result, (ii) not substantively fully correct, but plausible result, (iii) result is neither fully substantively correct nor plausible.